Emergence of melioidosis in Indonesia and today’s challenges - Tauran, P; Wahyunie, S; Saad, F; Dahesihdewi, A; Graciella, M; Muhammad, M; Lestari, D; Aryati, A; Parwati, I; Loho, T; Pratiwi, D; Mutiawati, V; et al. (MDPI, 2018)
A recent modeling study estimated that there could be as many as 20,000 human melioidosis cases per year in Indonesia, with around 10,000 potential deaths annually. Nonetheless, the true burden of melioidosis in Indonesia is still unknown. The Indonesia Melioidosis Network was formed during the first melioidosis workshop in 2017. Here, we reviewed 101 melioidosis cases (99 human and two animal cases) previously reported and described an additional 45 human melioidosis cases. All 146 culture-confirmed cases were found in Sumatra (n = 15), Java (n = 104), Kalimantan (n = 15), Sulawesi (n = 11) and Nusa Tenggara (n = 1). Misidentification of Burkholderia pseudomallei was not uncommon, and most cases were only recently identified. We also evaluated clinical manifestations and outcome of recent culture-confirmed cases between 2012 and 2017 (n = 42). Overall, 15 (36%) cases were children (age ; 15 years) and 27 (64%) were adults (age ≥15 years). The overall mortality was 43% (18/42). We conducted a survey and found that 57% (327/548) of healthcare workers had never heard of melioidosis. In conclusion, melioidosis is endemic throughout Indonesia and associated with high mortality. We propose that top priorities are increasing awareness of melioidosis amongst all healthcare workers, increasing the use of bacterial culture, and ensuring accurate identification of B. pseudomalleiand diagnosis of melioidosis.